Measurement of W±-boson differential cross-sections in proton–proton collisions with low pile-up data at √s = 5.02 TeV and 13 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Backes, Mathias; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Sanfilippo, Lorenzo; Sauer, Christof; et al. (The European physical journal. C, Particles and fields, 2025)
High precision single-differential W ±-boson production cross-sections as a function of electron or muon transverse momentum pT or their pseudorapity η, as well as double-differential cross-sections as functions of these variables, are measured in proton–proton collisions at centre-of-mass energies √s = 5.02 TeV and 13 TeV. The W -boson charge asymmetry as a function of lepton η is also measured. The data, collected in dedicated runs at reduced instantaneous luminosity with the ATLAS detector at the Large Hadron Collider, correspond to integrated luminosities of 255 pb−1 at 5.02 TeV and 338 pb−1 at 13 TeV. The measurements are in agreement with Standard-Model predictions calculated at next-to-next-to-leading-order in the strong coupling constant αs including transverse-momentum resummation at next-to-next-to-leading logarithmic accuracy using several parton distribution functions. The impact of the measured differential cross-sections as a function of lepton η on the determination of these functions is studied using a profiling technique
Im Titel ist das Plus-Minus-Zeichen hochgestellt
The ATLAS Collaboration: G. Aad, A. Ackermann, M.J. Backes, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, L. Sanfilippo, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, M. Wessels, J. Zinsser [und 2911 weitere]
Gesehen am 18.12.2025